2014 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2014
DOI: 10.1109/icassp.2014.6853797
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting transfer learning for personalized view invariant gesture recognition

Abstract: A robust gesture recognition system is an essential component in many human-computer interaction applications. In particular, the widespread adoption of portable devices and the diffusion of autonomous systems with limited power and load capacity has increased the need of developing efficient recognition algorithms which operates on video streams recorded from low cost devices and which can cope with the challenging issue of point of view changes. A further challenge arises as different users tend to perform t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…On the other hand, the emotion recognition module does not need to be constantly modified and is trained only once. While research has shown that personalizing emotion recognition in the context of continual learning increases performance [48,49], the same can be argued for action recognition (personalizing) [50,51]. In this work, we focus on IL in the context of allowing the addition of new classes to the system-personalized adaptation is out of our scope.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the emotion recognition module does not need to be constantly modified and is trained only once. While research has shown that personalizing emotion recognition in the context of continual learning increases performance [48,49], the same can be argued for action recognition (personalizing) [50,51]. In this work, we focus on IL in the context of allowing the addition of new classes to the system-personalized adaptation is out of our scope.…”
Section: Methodsmentioning
confidence: 99%
“…STTL is the process in which the source domain labels are available but the target is not, this is the validation stage in this study, when a calibrated model is benchmarked on further unknown data during application of a calibrated model. Transfer learning is the process of knowledge transfer from one learned task to another (Zhuang et al 2019), in this study, it is shown to be difficult to generalise a model to new subjects and thus application of a model to new data is considered a task to be solved by transfer learning; transfer learning often shows strong results in the application of gesture classification in related state-of-the-art works (Liu et al 2010;Goussies et al 2014;Costante et al 2014;Yang et al 2018;Demir et al 2019).…”
Section: Emg Gesture Classification and Calibrationmentioning
confidence: 97%